Correlation between electrochemical performance degradation and catalyst structural parameters on polymer electrolyte membrane fuel cell - Li Yunqi (Nanotechnology Reviews, 2019)
The catalysts performance degradation is a crucial issue in decay of the polymer electrolyte membrane fuel cell (PEMFC). The effect of Nafion content, dispersity of Pt nanoparticles and selected types of carbon support on the degradation of electrochemical surface area (ECSA) and double layer capacitance (DLC) were experimentally discussed by accelerated stress test (AST). The catalyst with 20wt% Nafion content exhibited better catalyst performance. i.e., the less DLC and ECSA degradation during AST. Catalysts with well Pt dispersity showed superior %ECSA (the percentage change of ECSA) retention. The heat-treated catalysts exhibited the lowest ECSA and DLC degradation rate due to the larger Pt particle and high carbon corrosion resistance. Moreover, a multi-order model describing the correlation between ECSA and DLC degradation was proposed, providing a vital reference for quantitatively investigating ECSA and DLC degradation in the catalysts with different catalysts structural parameters.